Pamięć Włoch Wojciecha Karpińskiego w perspektywie teorii neuroestetycznej Semira Zekiego - Trygar, Barbara (Poznańskie Studia Polonistyczne. Seria Literacka, 2019)
The aim of this article is to analyse Memory of Italy by Wojchech Karpinski in the in the prospect of the neuroaesthetic Semira Zeki theory. A works of art is an appropriately fabricated stimulus which is aimed at reprimanding the recipient. Evoking emotions at the spectator defined is included in nature of the works of art. The travel to Italy lets the hero experience the beauty, to find out the truth about world and about oneself, as well as to commune with the transcendental dimension.